Expanding syphilis test uptake using rapid dual self-testing for syphilis and HIV among men who have sex with men in China: A multiarm randomized controlled trial. - Cheng Wang; Jason J Ong; Peizhen Zhao; Ann Marie Weideman; Weiming Tang; M Kumi Smith; Michael Marks; Hongyun Fu; Weibin Cheng; Fern Terris-Prestholt; Heping Zheng; Joseph D Tucker; et al. (PLoS Medicine)
Background Low syphilis testing uptake is a major public health issue among men who have sex with men (MSM) in many low- and middle-income countries. Syphilis self-testing (SST) may complement and extend facility-based testing. We aimed to evaluate the effectiveness and costs of providing SST on increasing syphilis testing uptake among MSM in China. Methods and findings An open-label, parallel 3-arm randomized controlled trial (RCT) was conducted between January 7, 2020 and July 17, 2020. Men who were at least 18 years of age, had condomless anal sex with men in the past year, reported not testing for syphilis in the last 6 months, and had a stable residence with mailing addresses were recruited from 124 cities in 26 Chinese provinces. Using block randomization with blocks of size 12, enrolled participants were randomly assigned (1:1:1) into 3 arms: standard of care arm, standard SST arm, and lottery incentivized SST arm (1 in 10 chance to win US$15 if they had a syphilis test). The primary outcome was the proportion of participants who tested for syphilis during the trial period and confirmed with photo verification and between arm comparisons were estimated with risk differences (RDs). Analyses were performed on a modified intention-to-treat basis: Participants were included in the complete case analysis if they had initiated at least 1 follow-up survey. The Syphilis/HIV Duo rapid test kit was used. A total of 451 men were enrolled. In total, 136 (90·7%, 136/150) in the standard of care arm, 142 (94·0%, 142/151) in the standard of SST arm, and 137 (91·3%, 137/150) in the lottery incentivized SST arm were included in the final analysis. The proportion of men who had at least 1 syphilis test during the trial period was 63.4% (95% confidence interval [CI]: 55.5% to 71.3%, p = 0.001) in the standard SST arm, 65.7% (95% CI: 57.7% to 73.6%, p = 0.0002) in the lottery incentivized SST arm, and 14.7% (95% CI: 8.8% to 20.7%, p < 0.001) in the standard of care arm. The estimated RD between the standard SST and standard of care arm was 48.7% (95% CI: 37.8% to 58.4%, p < 0.001). The majority (78.5%, 95% CI: 72.7% to 84.4%, p < 0.001) of syphilis self-testers reported never testing for syphilis. The cost per person tested was US$26.55 for standard SST, US$28.09 for the lottery incentivized SST, and US$66.19 for the standard of care. No study-related adverse events were reported during the study duration. Limitation was that the impact of the Coronavirus Disease 2019 (COVID-19) restrictions may have accentuated demand for decentralized testing. Conclusions Compared to standard of care, providing SST significantly increased the proportion of MSM testing for syphilis in China and was cheaper (per person tested). Trial registration Chinese Clinical Trial Registry: ChiCTR1900022409.